Doctor's perspective for use of EHR visualization systems in public hospitals - Malik, M.S.A. (2013)
Efficient use of latest Electronic Health Records (EHR) focus on improved patient care using past patient data. Numerous EHR systems presented by different IT vendors, research groups and organizations for better visualization but still there is a gap of understanding and learning these systems for the physicians and doctors. This research work focuses on a detailed study with different set of doctors for their understanding and basic knowledge assessment about EHR in different public hospitals. The purpose of this study, is to identify the gap areas for data understanding of physicians non related to IT profession. Data have been gathered keeping four different criteria i.e doctor's belief, visualization knowledge set, assessment and future perspective for individual recommendations. This is all carried out with on the job working doctors and their understanding versus easiness perspective with different available EHR systems. Lesser knowledge about EHR applications pertaining to interface understanding, patient details visualization and comparision of multiple data set were observed as significant results. This will help to identify the weak knowledge operating areas of information visualization pertaining, to less experienced doctors at public hospitals using non unified procedures for EHR systems. Â© 2013 The Science and Information Organization.